Brain-Computer Interfaces Revolutionizing Human-Computer Interaction - Graimann, Bernhard; Pfurtscheller, Gert.; Allison, Brendan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
A brain-computer interface (BCI) establishes a direct output channel between the human brain and external devices. BCIs infer user intent via direct measures of brain activity and thus enable communication and control without movement. This book, authored by experts in the field, provides an accessible introduction to the neurophysiological and signal-processing background required for BCI, presents state-of-the-art non-invasive and invasive approaches, gives an overview of current hardware and software solutions, and reviews the most interesting as well as new, emerging BCI applications. The book is intended not only for students and young researchers, but also for newcomers and other readers from diverse backgrounds keen to learn about this vital scientific endeavour.
Introduction -- Neurophysiological and Neuropsychological Background -- Signal Processing -- Non-Invasive Approaches -- Invasive Approaches -- Hardware and Software -- Applications.
Keywords: Medicine; Neurosciences; Neurology; Neurosurgery; Neurobiology; Systems engineering; Biomedical engineering; Medicine & Public Health; Neurology; Circuits and Systems; Biomedical Engineering; Neurosciences; Neurosurgery; Neurobiology